Nitrate uptake by p-phosphonic acid calix[8]arene stabilized graphene - Eroglu, Ela; Zang, W.; Eggers, P.; Chen, X.; Boulos, R.; Wahid, M.; Smith, S.; Raston, C. (2013)
In situ sonic probe exfoliated graphene sheets in the presence of various concentrations of p-phosphonic acid calix[8]arene are effective in removing nitrate from aquatic effluents, with the efficiency increasing for higher ratios of calixarene to graphite. Mild sonication of the nitrate-adsorbed material releases some nitrate ions back to the effluent. © 2013 The Royal Society of Chemistry.